A Peran Dukungan Sosial Dalam Mengurangi Stres Adademik Dan Meningkatkan Motivasi Belajar Mahasiswa Kelas Karyawan - Andini (Jurnal Mahasiswa Manajemen, 2025)
Background – working students face dual demands than often tringger academic stress and reduce motivation. Social support has been shown to help them manage these pressures. Objective – This study reviews how social support relates to academic stress and learning motivation among working students. Design / Methodology / Approach – a literature review of five relevant articles (2020-2024) sourced from Google Scholar, SINTA, and ResearchGate Findings – Social support reduces academic stress and increases learning motivation. Emotional regulation and time management also help student balance work and study. Research Implication – The result emphasize the importance of strenghthening support systems for working student. Limitations – This review does not specify which types of social support are most effective and is limited to studies published between 2020-2024